2013
DOI: 10.1042/cs20130140
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in control of blood pressure

Abstract: In recent years the interest in studying the impact of sex steroids and gender on the regulation of blood pressure and cardiovascular disease has been growing. Women are protected from most cardiovascular events compared to men, until after menopause, and postmenopausal women are at increased risk of cardiovascular complications compared to premenopausal women. The pathophysiological mechanisms have not been elucidated but are not likely as simple as the presence or absence of estrogens, since hormone replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
141
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(161 citation statements)
references
References 73 publications
(94 reference statements)
11
141
1
8
Order By: Relevance
“…Several studies have shown that premenopausal women are protected from most cardiovascular events as compared with men (26). However, after the menopause, women are at an increased risk of cardiovascular complications as compared with premenopausal women (26). The pathophysiological mechanisms for such differences are not clear, but studies have shown that sex steroids make some contribution (30,36,42).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have shown that premenopausal women are protected from most cardiovascular events as compared with men (26). However, after the menopause, women are at an increased risk of cardiovascular complications as compared with premenopausal women (26). The pathophysiological mechanisms for such differences are not clear, but studies have shown that sex steroids make some contribution (30,36,42).…”
mentioning
confidence: 92%
“…Basic and clinical investigations have shown important differences in the structure and function of the cardiovascular system between men and women (32). Several studies have shown that premenopausal women are protected from most cardiovascular events as compared with men (26). However, after the menopause, women are at an increased risk of cardiovascular complications as compared with premenopausal women (26).…”
mentioning
confidence: 99%
“…[3][4][5] While benefits of soy-based consumption on blood pressure and other parameters of cardiovascular health have been relatively widely described, [6][7][8] the long-term effects of genistein in relevant experimental models remain relatively unclear. We have shown that administering genistein for a period of 2 days by subcutaneous injection at the concentration of 250 mg/kg body weight in the ovariectomized (OVX) rat causes a dose-dependent increase in cardiac output in isolated working hearts and increased ischemic tolerance to reperfusion injury.…”
mentioning
confidence: 99%
“…Moreover, it has shown that the incidence of CVD in women increases after menopause 15 . It is believed that sex hormones play a major role and estrogen deficiency might be the primary cause of this phenomenon in women in climacteric period; however, most of studies are based on experimental studies, using ovariectomized animals or isolated cells 16 . Although no changes in blood pressure values were found in trained HT group, AET was effective in promoting increase in cardiovascular biomarkers that play a crucial role on BP regulation or oxidative stress modulation.…”
Section: Discussionmentioning
confidence: 99%